Faktor Faktor yang Memengaruhi Minat Beli Ulang di Digerati House Bekasi - Dewianti Surya Pratiwi; Yudhiet Fajar Dewantara (Universitas Batanghari, 2023)
There are many factors that can influence consumer attitudes when making a purchase of a product or service, and when consumers are satisfied with the product or services purchased, it can imply on the intensity of making re-purchase in the future. Based on observations and reviews, there are 3 (three) most dominant factors of customer satisfaction that can affect interest in re-purchase and supported by increased sales in the coffee menu category. The aim of this study is to know the great influence of servicescape, campaign messages, and quality of coffee products on re-buy interest in Digerati House Bekasi. The research method used is quantitative using the method of analysis PLS (Partial Least Square), the sample in this study amounted to 100 respondents with the criterion of having made purchases more than 2 (two) times in Digarati House bekasi. The results of this study were that servicescape had a positive and significant influence on re-purchase intention with Tstatistic > Ttable (4,186 > 1,984) and p-value < 0,05, campaign messages had a significant and positive influence on re-purchase intention with TStatistic> Ttable (2,291 > 1, 984) and the p-value was < 0,05 and the quality of coffee products had a positive and significant influecne on re-purchase intention with Tstatistic > Ttabel (2,175 > 1, 984) and p-value < 0, 05.